Pengaruh Academic Self Concept terhadap Student Engagement pada Mahasiswa Fakultas Psikologi Universitas “X” Bandung - Ciptaning Putri Kukuh Kusuma Pratiwi; Jihan Eka Aulianti (Universitas Kristen Maranatha, 2024)
This research aims to investigate the influence of Academic Self Concept on the level of Student Engagement among students at the Faculty of Psychology, Universitas “X” Bandung. The background of this study is grounded in the significance of Student Engagement in learning and how Academic Self Concept, as a psychological factor, can affect the level of engagement. This research employs a quantitative approach with a descriptive analytical research design and a causal-explanatory type. The research method involves sampling students from the 3rd, 5th, and 7th semesters using purposive sampling techniques. Data were obtained through a questionnaire covering Academic Self Concept and the level of Student Engagement. Data analysis was conducted using correlation and regression tests to examine the relationships and influences between variables. The results indicate a positive and significant influence between Academic Self Concept and Student Engagement. Students with high levels of Academic Self Concept tend to exhibit higher levels of engagement in the academic environment. BAcademic Self Conceptd on the research results, practical suggestions include the development of integrated Academic Self Concept coaching programs within the curriculum, facilitating students' access to academic support resources, and organizing seminars and workshops on strategies to enhance Student Engagement. Strengthening these programs is expected to create a more supportive learning environment, motivate students, enhance Academic Self Concept, and ultimately improve the quality of learning in the Faculty of Psychology, Universitas “X” Bandung.